A educação cooperativa como ferramenta de desenvolvimento do cooperativismo: uma análise do trabalho desenvolvido pelo sistema ocb-sescoop/PA. - Santos, Carlos antonio Oliveira dos (Universidade Federal do Tocantins, 2023)
The article makes a literature review on cooperative education, bringing their importance and challenges to the peculiarities of cooperative enterprises, highlighting the importance of the Membership Organization (OQS) as an important education tool. Thus, it becomes inevitable to bring into question the distinction between cooperative education and training. In the field research were conducted semi-structured interviews with the contribution of a semistructured form with open and closed questions, with the aim of contributing to the research objective: raising activities, education programs and actions cooperative that the SISTEMA OCB-SESCOOP/PA developed in the years 2014 and 2015 for its member cooperatives, and compare them with the cooperative education activities for two cooperatives located in the city of Belém. Keywords: Corporate Education, Training, Cooperatives, Cooperative.